(untitled) (Journal of the College of Education for Women, 2019)
AbstractThis study concerned of scientific analysis of sociological directionsamong Iraqi scholars graduated before 1960. These directions was dividedbetween heritage, conflict, critical and symbolic interaction. It is important tomention that Al-Wardi scholar tried to build a theory in Sociology focused onthe image of Iraqi personality through historical approach used by Arabianscholar Ibn-Khaldon.